Biosynthesis of the Insecticidal Xenocyloins in Xenorhabdus bovienii. Issue 3 (10th February 2014) - Proschak, Anna; Zhou, Qiuqin; Schöner, Tim; Thanwisai, Aunchalee; Kresovic, Darko; Dowling, Andrea; ffrench‐Constant, Richard; Proschak, Ewgenij; Bode, Helge B.
Abstract The biosynthesis gene cluster for the production of xenocyloins was identified in the entomopathogenic bacterium Xenorhabdus bovienii SS‐2004, and their biosynthesis was elucidated by heterologous expression and in vitro characterization of the enzymes. XclA is an S‐selective ThDP‐dependent acyloin‐like condensation enzyme, and XclB and XclC are examples of the still‐rare acylating ketosynthases that catalyze the acylation of the XclA‐derived initial xenocyloins with acetyl‐, propionyl‐, or malonyl‐CoA, thereby resulting in the formation of further xenocyloin derivatives. All xenocyloins were produced mainly by the more virulent primary variant of X. bovienii and showed activity against insect hemocytes thus contributing to the overall virulence of X. bovienii against insects.